Modern economic theory: micro and macro analysis, money and banking, international economics, public finance, economic systems, economics of development and planning and economics of welfare - Dewett, Kewal Krishan; Chand, Adarsh (New Delhi, Shyam Lal Charitable Trust; sole distributors: S. Chand, 2002)
Covers micro and macro analysis, money and banking, international economics, public finance, economic systems, economics of development and planning and economics of welfare.
Includes bibliographical references and index.
oif 12/02/15.
Loan.
Keywords: Economics; Economic theory; Macroeconomics; Demand and supply; Microeconomics